The Relationship Between Knowledge Level and Vulva Hygiene Behavior During Menstruation in Adolescents - Ardianingrum, Vania; Muhlisin, Abi (Indonesian Journal of Global Health Research, 2024)
Good reproduction is a state that includes physical, mental, and social related to organs, functions, and reproductive processes. Menstruation is one of the signs of the maturity of the female reproductive organs, therefore knowledge of vaginal hygiene is required. The purpose of this study is to determine the relationship between the level of knowledge and behavior of vulvar hygiene during menstruation in adolescents. The type of research used is quantitative research using a cross sectional approach and data collection through questionnaires that have been tested for validity and reliability. The respondents involved in this study were adolescents at SMK 1 Juwiring with a total of 88 samples from 360 students. The results showed that there was a significant relationship between the level of knowledge and behavior of vulvar hygiene during menstruation in adolescents, with a significant p-value of 0.024 (< α 0.05), which stated a weak correlation with a value of r = 0.241, using the Spearman rho test. In conclusion, there is a relationship between the level of knowledge and vulva hygiene behavior during menstruation in adolescents at SMK 1 Juwiring with a positive direction, the higher the level of knowledge, the better the vulva hygiene behavior carried out.